Length–Weight and Girth Relationship, Condition Factor, and Stomach Contents of Pila Ovata from Otuoke/Otuaba River, Bayelsa State, Nigeria - Bubu-Davies O.A; Ogidiaka-Obende E.; Oyovwi T. (International Journal of Marine Life, 2025)
Otuoke/Otuaba River situated in Otuoke, Bayelsa State, Nigeria serves numerous purposes, such as fishing, laundry, human feacal disposal, amongst others. The river is home to Pila ovata, a mollusc which serves as a special delicacy in the meals of most Bayelsan due to its high protein content. The length-weight and girth relationship, condition factor and stomach contents of P. Ovata (Apple snail) from Otuoke/Otuaba River was studied. Snail samples were collected manually (handpicking) for a period of 5 weeks (May–June 2021). A total of 500 apple snails of varying sizes were analyzed. Results revealed negative allometric growth pattern for various relationships including length–weight relationship, shell length and shell width relationship, spiral length weight relationship, base length and weight relationship of P. ovata indicating a sigmoid growth pattern, slowing down after 5 weeks of life. The mean daily growth rates for all four subspecies ranged from 0.21–0.25 mm/day in the first 5 weeks, decreasing to 0.11–0.13 mm/day thereafter. The overall mean condition factor (0.02554) indicated that P. ovata was in good condition. Notably, the condition factor exceeded 1 during May and June, suggesting optimal health. Further research is necessary to fully understand the growth patterns and condition of P. ovata, as this study was limited to 5 weeks. In addition, urgent steps should be taken in the right direction to reduce the pollution load that has plagued the environment which these priced species thrive to avoid extinction.
Keywords: Growth pattern; Otuoke/Otuaba River; Pila ovata; food and feeding habits; wellbeing